Richard T. Ely's critique of capitalism - Bradizza, Luigi; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2013)
This book examines the work and thought of Richard T. Ely in light of his rejection of capitalism and view toward individualism. It concludes that there are real problems with Ely's theories and the principles of Progressivism, and addresses the implications of this for current American political thought.
Keywords: Political science; Political theory; World politics; Europe -- Politics and government; Political philosophy; Political Science and International Relations; Political Theory; Political Philosophy; European Politics; Political Science; Political History